REVIEW OF IMPORTANCE OF RAKTA IN RELEVANCE WITH SHARIRRACHANA - Kulkarni Prajkta Milind (International Journal of Applied Ayurved Research, 2015)
Rakta dhatu is one of the seven dhatus described in ayurveda. It has the prime most importance in the life of all pranimatras. In this article, the role of rakta dhatu is described concerning various aspects of sharir rachana like dashapranayatanas, pranadharaana, kala,strotas, twacha, matrujabhav, avayavautpatti in garbhavastha, ashaya, marmasambandh. Also rakta nirmiti, its upadhatu, mala, praman, gunas, panchbautikatva have been decribed.